(untitled) (Journal of Comparative & International Higher Education, 2022)
This article explores the educational processes of the high-school youth and higher education youth of parents who were imprisoned following the coup attempt in Turkey in July 2016. Data was collected from parents who are involved in their children’s education and who have been subjected to political persecution. The research is focused on educational processes with respect to students’ academic success, psychological problems, and changes to moral and universal values, all from the point of view of the parents. The main conclusions seem to be that the majority of students whose parents were imprisoned had to change their schools, their academic success decreased, the students who continued their higher education were prolonged or had to leave their schools, and the majority of them did not have serious psychological problems. Finally, the sense of injustice they felt when their parents were arrested, students seem to question universal and moral values.